2022
DOI: 10.1038/s41598-022-26021-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered synthesis of phytochemical-adorned green silver oxide (Ag2O) nanoparticles via Mentha pulegium and Ficus carica extracts with high antioxidant, antibacterial, and antifungal activities

Abstract: Silver oxide nanoparticles have various biomedical and pharmaceutical applications. However, conventional nanofabrication of Ag2O is associated with the use of toxic chemicals and organic solvents. To circumvent this hurdle, herein silver oxide quantum dots (Ag2O-QDs) were synthesized quickly (3 min) via the use of ultrasonic irradiation and plant-extract. Additionally, due to ultrasonic irradiation's effect on cell-wall destruction and augmentation of extraction efficiency, ultrasonic was also used in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…[ 43 ] There was a decrease in the crystalline size of the sample which can increase the surface‐to‐volume ratio and provide more active sites which enhances contact and friction and allows the sample to enter the cell through the pores of plasma membrane proteins, triggering cell death. [ 44 ] Also, A smaller band gap and enhancement in the surface area of the sample make the material more efficient at generating reactive oxygen species (ROS) when exposed to light and provide more active sites for reaction. The generation of ROS, such as superoxide radicals (O2•−) and hydroxyl radicals (•OH), is a key mechanism through which these materials exhibit antifungal activity.…”
Section: Resultsmentioning
confidence: 99%
“…[ 43 ] There was a decrease in the crystalline size of the sample which can increase the surface‐to‐volume ratio and provide more active sites which enhances contact and friction and allows the sample to enter the cell through the pores of plasma membrane proteins, triggering cell death. [ 44 ] Also, A smaller band gap and enhancement in the surface area of the sample make the material more efficient at generating reactive oxygen species (ROS) when exposed to light and provide more active sites for reaction. The generation of ROS, such as superoxide radicals (O2•−) and hydroxyl radicals (•OH), is a key mechanism through which these materials exhibit antifungal activity.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been found that MgONPs have the ability to breach the plasma and outer membranes, which depletes intracellular ATP [ 67 ]. Another hypothesis that has been proposed is that oxygen and silver interact with sulfhydryl moieties on the cell wall to form R-S-S-R bonds, which stop the cell from breathing and force it to die [ 68 ]. Moreover, recent study evidence has indicated that MgONPs may have antimicrobial effects on microorganisms by accelerating the release of ROS, which causes intracellular material to escape through membranes, harming DNA and proteins, and releasing cellular content, and eventually causing cell death[ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was because an acidic pH makes the process of bio-component denaturation significantly simpler. The extracts of F. carica are rich in phytochemical components, including flavonoids and phenolic acids, which are the most important contributing chemicals that take part in the manufacturing of NPs [ 20 , 21 ]. All the bio components that have been discussed up to this point are very effective as capping and reducing agents of metal ions, and as a result, they are directly involved in the biological formation of nanomaterials [ 12 ].…”
Section: Resultsmentioning
confidence: 99%